Metafisika Mimpi: Telaah Filsafati terhadap Teori Mimpi C.G. Jung (1875-1961) - Nur, Muhammad (Jurnal Filsafat "WISDOM", 2004)
A dream has been a part of human life. It's a universal phenomenon playing an important role in building culture of human being althought it is experience. It is also a thing embedding a human life. The discource of dream, so far, isn't not dominated by both one community and one knowledge discipline. But, it does several disciplines for instace; philosophy, psychology, religion, etc. It proved that dream discourse is extremly open to study because of its interesting and actual object/ Moreover, in field academic, the dream is more popular and well-known by psycolog with its psychology as discipline but this paper isn't triying to built dream from psychological approach. Although Carl Gustav Jung as the expret whom I will study is a psycolog that concerns dream theories but I will try to see aspects of philosophical metaphysis from those Jung's theories.I am of descriptive-analitycal method to use. I am trying to describe Jung's terminoligies and keywords then to search the background of his thought construction. From this point of view, I am trying to analyze it in order to find the aspects of philosophical metaphysic from those Jung's theories.Carl Gustav Jung is Sigmund Freud's student. While taking several teachers theories, Jung didn't have same idea. It's because his teacher tends to sexuality and both materialist and biological oriented in explaining his theories. Jung's doctrine which is well-known as analytical psychology is strongly stated by myth, mysticism, metaphysic and religious experience. He believes that those are more relevant to desribe well on human spirituality, on the other side, Freud's theories has just touched materialistic ones.Accordin to Jung, personality is the compromised combination between the inner life and the out world. Therefore, according to Jung, dream is a proof of exsisting dimension of innate religious because, recently, dreams describe by classic and modern people are desribed psychological paradigm about the relation between human being and spiritual world. Through analyzing dream from any psychological aspect, he concludes it is the existence of religious inner power that manifest the form of glorying and sacralizing thing in the human life.